Knowledge sharing and transfer in an open innovation context: Mapping scientific evolution - Izaskun Alvarez-Meaza; Naiara Pikatza-Gorrotxategi; Rosa Maria Rio-Belver (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
The essence of innovation lies in knowledge, which is why open innovation opens the door to knowledge transfer with agents outside the organization. In order to comprehend the joint scientific trajectory of these two areas of knowledge, the aim of this study is to identify and analyze the main indicators of scientific behavior involved in the research field related to the link between open innovation and knowledge transfer or knowledge sharing concepts through bibliometric and network analysis. The results show clear European leadership in scientific production developed in universities. In addition, the high quality of the main sources of diffusion infers publications of good scientific quality. The most recognized source of knowledge used in new research is directed towards university-company relationships in an open innovation environment. Network analysis related to keywords has allowed us to define the most interesting, relevant fields of research, highlighting the importance acquired by topics such as 'communication', 'inter-organizational context' and 'education', to better focus on future research of the scientific community. It can be concluded that the scientific development of both concepts is an active field in the academic community, and also, that new key terms appear, opening new paths of research.
Keywords: 650; open innovation; knowledge sharing; knowledge transfer; bibliometric analysis; network analysis